Naming and Knowing Revisited: Eyetracking Correlates of Anomia in Progressive Aphasia - Ungrady, Molly B.; Flurie, Maurice; Zuckerman, Bonnie M.; Mirman, Daniel; Reilly, Jamie (Frontiers in Human Neuroscience, 2019)
Progressive naming impairment (i.e., anomia) is a core diagnostic symptom of numerous pathologies that impact anterior and inferior portions of the temporal lobe. For patients who experience such regional temporal lobe degeneration, patterns of language loss often parallel the degradation of semantic memory, an etiology of naming impairment known as semantic anomia. Previous studies of semantic anomia have focused extensively on the output of naming attempts by contrasting errors, omissions, and distortions as a function of item-level characteristics (e.g., prototypicality, semantic category). An alternative approach involves evaluating visual confrontation naming as the naming process unfolds. Techniques with high temporal resolution (e.g., eyetracking) offer a potentially sensitive mode of delineating the locus of impairment during naming. For example, a lexical retrieval disorder would hypothetically elicit normal gaze patterns associated with successful visual object recognition regardless of naming accuracy. In contrast, we hypothesize that semantic anomia would be distinguished by aberrant gaze patterns as a function of reduced top-down conceptually guided search. Here we examined visual object recognition during picture confrontation naming by contrasting gaze patterns time locked to stimulus onset. Patients included a cohort of patients with anomia associated with either primary progressive aphasia (N=9) or Alzheimer’s disease (N=1) who attempted to name 200 pictures over the course of 18-24 months. We retrospectively isolated correct and incorrect naming attempts and contrasted gaze patterns for accurate vs. inaccurate attempts to discern whether gaze patterns are predictive of language forgetting. Patients tended to show a lower fixation count, higher saccade count, and slower saccade velocity for items that were named incorrectly. These results hold promise for the utility of eyetracking as a diagnostic and therapeutic index of language functioning.